Pengaruh Latihan Jump Box dan Lompat Gawang Terhadap Hasil Lompat Jauh Pada Ekstrakurikuler Atletik di SMA Negeri 1 Bangsri - Muhammad Rizqi David Saputra; Agus Widodo Suripto (Indonesian Journal for Physical Education and Sport, 2024)
Athletics, especially the long jump number at SMA N 1 Bangsri is one of the lessons that students are interested in. This study aims to determine the effect of jump box and jump goal training on long jump results in extracurricular athletics at SMA Negeri 1 Bangsri. This study uses an experimental approach with test techniques in data collection. The results of the study through the t test (paired t test) on jump box training obtained a significance value (2-tailed) of 0.005 <0.05, which means that the hypothesis is accepted. This states that jump box training has an effect on the results of long jumps in extracurricular athletics at SMA Negeri 1 Bangsri. Meanwhile, the jump goal exercise obtained a significance value (2-tailed) of 0.000 <0.05, which means that the hypothesis is also accepted. This states that goal jump training has an effect onthe results of the long jump in extracurricular athletics at SMA Negeri 1 Bangsri. The conclusion and results of this study are that there is an effect of jump box training and goal jump training on the results of long jumps in extracurricular athletics at SMA Negeri 1 Bangsri, so that teachers or athletic coaches at SMA Negeri 1 Bangsri can use jump box training and goal jump training to improve student long jump results.